Konsep Belajar dalam Perspektif Imam Al-Ghazali dan Imam Al-Zarnuji: Analisis Komparatif dan Relevansinya terhadap Pendidikan Kontemporer - Nur Alfil Lail; Mamluatul Ilmiyeh; Ikmal Muhammad; Amelia Divina Putri; Emna Laisa (IHSANIKA : Jurnal Pendidikan Agama Islam, 2026)
This research aims to explore the concepts of learning according to Imam Al-Ghazali and Imam Al-Zarnuji, while examining their similarities and differences. It also investigates their relevance to contemporary education. The study employs a qualitative method through library research, drawing data from relevant books, classical texts, and scientific journals. Data collection is conducted via documentation, followed by descriptive-analytical analysis.The findings reveal that both scholars share similarities in emphasizing the importance of spiritual aspects, morals, and intention in the learning process as a means to draw closer to Allah SWT. However, differences exist in their focus: Imam Al-Ghazali places greater emphasis on the teacher's role as a primary role model, whereas Imam Al-Zarnuji highlights learning ethics and the teacher-student relationship.The learning concepts from these two figures are highly relevant to modern education, particularly in character building, sincerity, discipline, and balancing cognitive, affective, and spiritual dimensions. Thus, integrating the thoughts of Imam Al-Ghazali and Imam Al-Zarnuji can serve as a foundation for developing a more holistic and meaningful educational system.